Strategy of the Agriculture and Food Security Office of Sumedang District in Optimizing the Productivity of Food Crops and Horticultural: (Study of Farmer Empowerment in Pamulihan Sub-District Sumedang Regency In 2022 – 2023) - Tiyan Rahmanul Hakim; Gun Gun Gunawan; Novie Indrawati Sagita (Rescollacom (Research Collaborations Community), 2025)
The purpose of this research is to describe and analyze farmer empowerment strategies in Pamulihan Sub-District, Sumedang Regency. Pamulihan sub-district has agricultural potential, especially food crops and various kinds of horticulture, so the Department of Agriculture and Food Crops of Sumedang Regency needs to optimize this potential through increasing agricultural productivity. This research uses qualitative methods with data collection techniques through interviews, observation, and documentation. Informants taken in this study included the Food Crops and Horticulture Division, Food Crops and Extension Division, Pamulihan area Technical Implementation Unit/Field Agricultural Extension Workers, and Farmers. The selection of informants used purpose sampling technique. After the data was collected, it was followed by data analysis, namely data reduction, data presentation and conclusion drawing. Then the data was tested for validity using triangulation of sources and techniques. This is intended so that the validity of the data can be trusted. The five aspects of community empowerment strategies, namely human resource development, group institutional development, productive business capital fertilization, and provision of appropriate information, were used as analytical tools. The results showed that the Department of Agriculture and Food Security office of Sumedang Regency has empowered farmers in Pamulihan Sub-district quite well, as evidenced by the increase in food crop and horticultural production. However, the Department of Agriculture and Food Crops have not been maximized in fertilizing productive businesses, and developing farmers' economic institutions.